Percutaneous renal graft biopsy: a clinical, laboratory and pathological analysis - Mazzali, Marilda; Ribeiro-Alves, Maria Almerinda Vieira Fernandes; Alves Filho, Gentil (São Paulo Medical Journal, 1999)
CONTEXT: Renal allograft biopsies have been used as a good method for monitoring the evolution of kidney transplants for at least 20 years.1 Histological analysis permits differential diagnosis of the causes of allograft dysfunction to be made. OBJECTIVES: To correlate the data of urinalysis and serum creatinine with histological diagnosis of renal graft in a group of renal transplant patients. DESIGN: Accuracy study, retrospective analysis. SETTING: A university terciary referral center. SAMPLE: 339 percutaneous allograft biopsies obtained from 153 patients. Blood and urine samples were obtained before the graft biopsy. MAIN MEASUREMENTS: Laboratory evaluation and hystological analysis (light microscopy, imunofluorescent eletronic microscopy). RESULTS: Most of the biopsies (58.9%) were performed during the first month post-transplant. An increase in serum creatinine was associated with acute tubular and/or cortical necrosis. Proteinuria and normal serum creatinine were associated with glomerular lesions. Non-nephrotic range proteinuria and an increase in serum creatinine were associated with chronic rejection. CONCLUSIONS: Evaluation of serum creatinine and urinalysis can be useful in suggesting the histological graft diagnosis.